Developing awareness of unknown sounds to improve merging and substitution pronunciation mistakes - Almeida, Evelyn (2018)
Although emphasis on teaching pronunciation of a second language has been almost null among EFL educators and researchers, recent studies portray pronunciation as a key factor to learn a second language. This paper reviews literature of experts on the field who highlight the relevance of teaching pronunciation. In order to provide the readers with a theoretical basis the paper first presents a review of recent discussions on the necessity to teach pronunciation. Then it offers a description of the features of pronunciation, influential factors, problems such as merging and substitution caused by the differences between the First and Second Language phonological system, and teaching methodologies. Out of this context, we have favored one of the approacheswhich shed light on the development of pronunciation awareness. Finally some activities which aim to help learners pronounce unknown sounds in a clear and intelligible way are proposed.